Implementation of Bai'at in Strengthening Religious Moderation Attitudes among Students - Rukman, Rukman; Rahman, Mohammad Taufiq; Wibisono, M. Yusuf (UIN Sunan Gunung Djati Bandung, 2024)
This study explores the role of the Bai'at Santri at the Islamic Boarding School (Pesantren) of Pangalengan in strengthening religious moderation among students. To achieve these objectives, the research employs a qualitative method with a positivist approach, enabling an in-depth exploration of data within its natural context. Data were collected through triangulation techniques, and the analysis was conducted qualitatively using an inductive approach based on existing facts. The findings indicate that the Bai'at Santri at the pesantren is not an extremist ritual, but rather a pledge by students to adhere to the pesantren's rules and respect the values of Islamic moderation. This activity supports the indicators of religious moderation developed by the Indonesian Ministry of Religious Affairs, such as national commitment, tolerance, non-violence, and accommodation of local culture. Through Bai'at Santri, students are expected to develop moderate attitudes, which include understanding differences, applying just laws, and utilizing science and technology to solve problems. This study concludes that Bai'at Santri is proven to be an effective strategy in strengthening religious moderation at PPI 259. This activity not only fosters tolerance among students but also reinforces the integration of moderation values into daily life at the pesantren. Future research is recommended to explore the long-term impact of Bai'at Santri on the surrounding community and to analyze factors that can enhance the effectiveness of religious moderation programs at other pesantren. Additionally, the perspectives of students and alumni should be considered to gain deeper insights into the influence of Bai'at Santri on their attitudes and behaviors after leaving the pesantren.